Model Productive Parenting pada Remaja di Kota Bandung - Ellen Theresia; O. Irene Prameswari Edwina (Universitas Kristen Maranatha, 2023)
Parents are significant figures for children and have a crucial role to build children's character, especially through parenting. When children become teenagers, parents also need to adjust the parenting given. The parenting focus of the research is productive parenting, which is a parenting pattern with warmth, acceptance, firm and clear control, demands according to the child's age, being responsive and making children the main priority. Purpose of this study is to develop a factor model of productive parenting as a construct, based on the integration of aspects: high parental acceptance and warmth, moderate to high restrictiveness, insistence on mature behavior, high responsiveness, and high positive involvement. Researchers adds parental modeling as an important aspect of productive parenting. Based on 816 participants, our CFA displays all aspects High parental acceptance and Warmth, moderate to high restrictiveness, Insistence on mature behavior (demand), High responsiveness, High positive involvement and Parental modeling, are constructs of productive parenting.